Endoscopic and videofluoroscopic evaluations of swallowing for dysphagia: A systematic review - Mario Augusto Ferrari de Castro; Rogério Aparecido Dedivitis; Leandro Luongo de Matos; José Carlos Baraúna; Luiz Paulo Kowalski; Kauê de Carvalho Moura; Daniel Herman Partezani (Brazilian Journal of Otorhinolaryngology)
Objective: This systematic review was performed to compare the diagnostic accuracy of FEES and VFSS in evaluating swallowing in adults with dysphagia. Methods: A search for articles published between January 1991 and March 2020 was carried out in the MEDLINE EMBASE, COCHRANE, SciELO, and LILACS electronic databases. Based on the eligibility criteria, six articles were included. Results: FEES demonstrated a higher ability to diagnose pharyngeal residue, penetration, and aspiration compared with VFSS, and slightly better performance in detecting premature spillage. Conclusion: There were no significant differences on the diagnostic performance of both tests. The choice of test should depend on availability, team experience, and patient’s preference. Level of evidence: Level III.